Genome-wide association study to identify the genomic loci associated with wheat heading date variation under autumn-sowing conditions - Yurim Kim; Myoung-Goo Choi; Myoung Hui Lee; Chuloh Cho; Jun Yong Choi; Suk-Jin Kim; Chon-Sik Kang; Chul Soo Park; Ki-Chang Jang; Youngjun Mo; Changhyun Choi (PLoS ONE, 2025)
The present study aimed to identify genetic loci associated with days to heading (DTH) in wheat under autumn-sowing conditions in Korea, where early heading is critical owing to the overlap between the wheat harvest and the rainy season. We evaluated 530 wheat core collections over five years, focusing on known heading date genes VRN-1 and PPD-1, and conducted a genome-wide association study (GWAS) to identify new genetic loci related to DTH. The results revealed that Korean accessions exhibited the earliest DTH, with modern Korean varieties heading even earlier, reflecting a strong breeding focus on early heading. Among the existing heading date genes, VRN-1 and PPD-D1 were significantly associated with DTH in the wheat core collection. However, all Korean varieties carried the same alleles for each of VRN-A1, PPD-A1, and PPD-D1, resulting in low genetic diversity, which rendered the existing heading date genes insufficient to fully account for the variation in DTH within the Korean varieties. GWAS identified nine single nucleotide polymorphisms (SNPs) associated with DTH in Group A (entire collection filtered, n=518) and six in Group B (accessions with genotypes identical to Korean varieties filtered, n=231). Four key SNPs (AX-95222044 and AX-94685526 in Group A, and AX-94550996 and AX-94970315 in Group B) were selected based on their effect sizes on DTH. In both groups, accessions with alleles for early heading at both of the selected SNPs exhibited the earliest DTH, advancing by 7.7 to 8.9 days. These findings suggest that the selected SNPs, particularly those reflecting the genotypes of Korean varieties, effectively explain the variations in DTH among Korean varieties and could enhance wheat breeding efficiency in Korea. Further research is needed to validate the four selected SNPs and identify the underlying genes, which could serve as valuable markers for developing early-heading wheat varieties suited to Korean autumn-sowing conditions.